LEADING ARTISTIC FEATURES OF THE SHORT STORY GENRE IN UZBEK LITERATURE - Rakhmonova Khurshida (Web of Journals Publishing, 2024)
In this article, the history of the short story genre and its introduction into Uzbek literature were studied. The specific features of this genre were analyzed based on the short story "Question" by writer Khurshid Dostmuhammad. The system of images in the work, the writer's artistic concept is studied.
Keywords: Short story term, classic short story, traditional and realistic interpretations, symbolic images, fantastic stories.